Genomic analysis and antibiotic resistance of a multidrug-resistant bacterium isolated from pharmaceutical wastewater treatment plant sludge - Ningyu Sun; Hu Gao; Xinbo Zhang; Zeyou Chen; Anping Peng (Ecotoxicology and Environmental Safety)
Pharmaceutical wastewater treatment plants (PWWTPs) serve as reservoirs for antibiotic-resistant bacteria (ARBs) and antibiotic resistance genes (ARGs). In this study, a multiantibiotic-resistant strain of Acinetobacter lwoffii (named N4) was isolated from the dewatered sludge of a PWWTP. N4 exhibited high resistance to both antibiotics and metals, with minimum inhibitory concentrations (MICs) of chloramphenicol and cefazolin reaching 1024 mg·L−1 and MICs of Cu2+ and Zn2+ reaching 512 mg·L−1. Co-sensitization experiments revealed that when antibiotics are co-existing with heavy metal ions (such as TET and Cd2+, AMP and Cu2+) could enhance the resistance of N4 to them. Whole-genome sequencing of N4 revealed a genome size of 0.37 Mb encoding 3359 genes. Among these, 23 ARGs were identified, including dfrA26, bl2beCTXM, catB3, qnrB, rosB, tlrC, smeD, smeE, mexE, ceoB, oprN, acrB, adeF, ykkC, ksgA and sul2, which confer resistance through mechanisms such as efflux pumps, enzyme modification and target bypass. Additionally, the N4 genome contained 187 genes associated with human disease and 249 virulence factors, underscoring its potential pathogenicity. Overall, this study provides valuable insights into ARBs in PWWTPs and highlights the potential risks posed by multidrug-resistant strains such as N4.